Infographics as a Tool to Facilitate English Learning Activities: Student’s Perceptions - Arochman, Taufik; Jabbar, Sahda Aulia; Hutabarat, Putri Surya Padilla; Pitaloka, Nadia Sekar Ayu (Institut Agama Islam Negeri (IAIN) Curup, 2023)
The research focuses on the impact of infographics as a tool for English learning trough studentâ€™s perceptions. The purpose of this research is to identify the positive impact of using infographics for students' learning and teaching activities in the classroom and also the appropriate learning media by educators. The researchers used qualitative research methods in analyzing the data that was collected. The instrument of the research was a questionnaire that consists of questions and statements that must be filled in by the elected respondents. The questionnaire was targeted to students of Universitas Tidar, especially the student of the English Education Department study program in the second and fourth semesters. There were many as 41 participants as a sample in this study. The results of this study show that based on the students' experience of knowing and using infographics in the learning activity, most of them agree that the use of infographics as learning media has a very positive impact. Infographics are also the suitable medium to improve students' quality in understanding the material and their interest in learning.Â